Working-Time Configurations: A Framework for Analyzing Diversity Across Countries - Berg, Peter; Bosch, Gerhard; Charest, Jean (ILR Review, 2014)
Working-time practices across the developed world have exploded with diversity during the past few decades. The once standard 8-hour day and 40-hour workweek that emerged and reigned throughout much of the 20th century have given way to an increasing variety of working-time arrangements. Flexible schedules, in which hours can vary daily or weekly, and nonstandard work arrangements, such as fixed term, on-call, temporary, or part-time, are widely used at the workplace. In addition, we have witnessed the growth of zero-hour contracts that make no guarantee to provide workers with weekly working hours or a reliable income, while requiring employees to work on very short notice with very unpredictable schedules; annualized hours contracts that allow for work hours to vary over a year; and working-time accounts that allow employees to bank hours worked over a set weekly standard and to then draw on these accounts for paid time off.